2019
DOI: 10.1021/acs.jpcc.9b00593
|View full text |Cite
|
Sign up to set email alerts
|

Water Dynamics in Nanoporous Silica: Ultrafast Vibrational Spectroscopy and Molecular Dynamics Simulations

Abstract: Nanoporous silica materials are important in catalysis, energy, and materials applications in which water is an essential component. System performance is intimately connected to the water dynamics occurring in the confined environment. However, the dynamics and associated structures of water in nanoporous silica have proven challenging to measure and predict. Here, confined water dynamics are examined via the ultrafast infrared spectroscopy of selenocyanate (SeCN–) dissolved in the hydrated ∼2.4 nm silica mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
79
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(87 citation statements)
references
References 74 publications
(221 reference statements)
7
79
1
Order By: Relevance
“…While these approaches cannot generally describe chemical reactivity (outside of the SiO 2 solid), polarization, or charge-transfer effects, they have been successfully used to describe the phase behavior of silica as well as the properties of the amorphous solid. For example, they have been used effectively in describing the interactions of silica with liquids, , particularly for chemical phenomena that require long simulation times. , Several force fields have been shown to display transferability between crystalline phases and even to amorphous silica . Most of these force fields share a common structure of electrostatic interactions combined with shorter-ranged potentials describing van der Waals interactions. , They differ primarily in the quantitative balance between these two components as well as the form of the latter as either Buckingham, ,, Lennard-Jones, ,,, or Morse , potentials.…”
Section: Introductionmentioning
confidence: 99%
“…While these approaches cannot generally describe chemical reactivity (outside of the SiO 2 solid), polarization, or charge-transfer effects, they have been successfully used to describe the phase behavior of silica as well as the properties of the amorphous solid. For example, they have been used effectively in describing the interactions of silica with liquids, , particularly for chemical phenomena that require long simulation times. , Several force fields have been shown to display transferability between crystalline phases and even to amorphous silica . Most of these force fields share a common structure of electrostatic interactions combined with shorter-ranged potentials describing van der Waals interactions. , They differ primarily in the quantitative balance between these two components as well as the form of the latter as either Buckingham, ,, Lennard-Jones, ,,, or Morse , potentials.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the confinement effects on the orientational relaxation and spectral diffusion of the water in the nanopores of MCM-41 via PSPP spectroscopy and 2D infrared (IR) measurements, and MD simulations have also been reported. It is found that the dynamics of confined water shows a slower decay component which is not present in the bulk liquids . The simulated results of acetonitrile confined in the nanoscale silica pore demonstrates that the acetonitrile forms an antiparallel bilayer structure in which the acetonitrile closest to the pore surface shows an ordered behavior with the N atom pointing toward the pore wall.…”
Section: Introductionmentioning
confidence: 89%
“…The Lennard-Jones (L-J) potential was used to describe the interactions between the silica, MeIm, and MeSCN molecules. The parameters of the silica model were taken from the ClayFF model, , as shown in Table . The parameters taken from the OPLS-AA force field were employed to represent the MeIm and MeSCN molecules in which the L-J parameters for the C and N atoms on the CN groups of MeSCN were described by the ANL model .…”
Section: And Experimental Methodologymentioning
confidence: 99%
See 2 more Smart Citations